2017
DOI: 10.1007/s00404-017-4317-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of AKT1 along with AKT2 in granulosa-lutein cells of hyperandrogenic PCOS patients

Abstract: High expressions of AKT1 and AKT2 through possible relation with androgen may cause GCs dysfunction in the +HA PCOS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Which is in agreement with some reports in patients with PCOS or animal models of PCOS [16,17]. However, other studies reported that the PI3K/Akt signaling is overactivated in PCOS [32,33]. PCOS is a complex disease, and the PI3K/Akt signaling pathway is complicated and dependent on different cells and conditions, which may be the reason of the discrepancy results.…”
Section: Discussionsupporting
confidence: 91%
“…Which is in agreement with some reports in patients with PCOS or animal models of PCOS [16,17]. However, other studies reported that the PI3K/Akt signaling is overactivated in PCOS [32,33]. PCOS is a complex disease, and the PI3K/Akt signaling pathway is complicated and dependent on different cells and conditions, which may be the reason of the discrepancy results.…”
Section: Discussionsupporting
confidence: 91%
“…Follicular atresia is potentiated by androgens in the immature rat, and granulose cell apoptosis in rats is inducible by androgens [ 18 ]. Increased expression of AKT1 and AKT2 may be a possible mechanism linking HA to granulosa cell dysfunction in patients with HA PCOS [ 19 ]. Finally, testosterone may impact the endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the network analysis, we obtained three proteins of interest—AKT1, IL6 and INSR. In the hyper-androgenic PCOS patients, high levels of AKT1 have been associated with GCs dysfunction [ 43 ]. In addition, IL6, IL1B1 and TNF are associated with increased susceptibility to PCOS [ 44 ], and INSR plays a role in compensatory hyperinsulinemia [ 45 ].…”
Section: Discussionmentioning
confidence: 99%